The Eye : A Very Short Introduction - Land, Michael F. (Oxford Oxford University Press, 2014)
In this Very Short Introduction, Michael Land introduces all aspects of the eye and vision in both human and animals. He looks at the features of the human eye and retina, explores the evolution of eyes, and considers aspects of visual perception, including eye movements, vision in three dimensions, color vision, and visual recognition.
Include Illustrations and Index.
A Very Short Introduction.
Keywords: Vision -- Eye -- Eye--Growth